2014
DOI: 10.1002/ajpa.22554
|View full text |Cite
|
Sign up to set email alerts
|

Early life histories of the London poor using δ13C and δ15N stable isotope incremental dentine sampling

Abstract: High resolution incremental isotopic analysis of the dentine from early forming teeth, especially first molars (M1s), provides a means to assess the effects of poor childhood nutrition and healthcare on individuals in an assemblage where there are no infants to study. This approach is applied to an 18th and 19th century cemetery population associated with St Saviour's Almshouse burial ground in Southwark, London, to assess whether, or how, early dietary history, including weaning age, influenced health and nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 45 publications
3
95
0
1
Order By: Relevance
“…A re-examination of the previous studies which have used dentine sections to examine breastfeeding and weaning (Burt and Garvie-Lok 2013;Eerkens et al 2011;Eerkens and Bartelink 2013;Henderson et al, 2014Fuller et al 2003 shows that their data also demonstrate considerable isotope variability during infancy. Fuller et al (2003) use the means for each dentine section to match the current interpretation model, but if the data for each individual are analyzed, for five of the 21 deciduous teeth and two of the eight permanent teeth, the differences acknowledge that this may be due to differences either in breastfeeding/weaning behavior, or an increased male susceptibility to nutritional deprivation.…”
Section: Re-evaluating Previous Studiesmentioning
confidence: 93%
“…A re-examination of the previous studies which have used dentine sections to examine breastfeeding and weaning (Burt and Garvie-Lok 2013;Eerkens et al 2011;Eerkens and Bartelink 2013;Henderson et al, 2014Fuller et al 2003 shows that their data also demonstrate considerable isotope variability during infancy. Fuller et al (2003) use the means for each dentine section to match the current interpretation model, but if the data for each individual are analyzed, for five of the 21 deciduous teeth and two of the eight permanent teeth, the differences acknowledge that this may be due to differences either in breastfeeding/weaning behavior, or an increased male susceptibility to nutritional deprivation.…”
Section: Re-evaluating Previous Studiesmentioning
confidence: 93%
“…By applying the microsectioning method to permanent molars obtained from 18th and 19th century cemetery populations in London, Henderson et al (2014) revealed the intrapopulation variations in BWP. Furthermore, Burt and Garvie-Lok (2013) developed a new method of deciduous dentin micro-sampling for stable isotope analysis, which concentrates on the dietary signals of the pregnant mother, breast milk, and weaning foods.…”
Section: And Dmentioning
confidence: 99%
“…Furthermore, there are great individual variations in BWPs in modern traditional and industrialized human populations (Vitzthum, 1994). Individual variations in BWP cannot be discussed in most cross-sectional reconstructions, but can be in longitudinal reconstructions using isotopic signals in hair (Fuller et al, 2006a), serial sections of tooth dentin (Eerkens et al, 2011;Beaumont et al, 2013b;Eerkens and Bartelink, 2013;Henderson et al, 2014), and elemental signals in thin-sectioned tooth enamel (Humphrey et al, 2008a;Austin et al, 2013).…”
Section: Heterogeneous Bwps In One Study Groupmentioning
confidence: 99%
See 2 more Smart Citations